Characterization of falls among elderly rescued by the mobile first-aid service - Abrantes, Kennia Sibelly Marques de; Menezes, Taciana Nobre de; Farias, Maria do Carmo Andrade Duarte de; Silva, Maria Isabel Leandro da; Rolim, Vanessa Estrela; Macedo Junior, Hugo; Abreu, Luiz Carlos de (ABCS Health Sciences, 2013)
Introduction: Currently the increase in life expectancy has called attention to the health conditions during those extra years and the possibility of future incidences of morbidity and mortality and various health problems such as falls. Objective: To investigate the association between the characteristics of fall and age group. Methods: This was a cross-sectional study. Data were collected through a specific form in the months from March to June 2012 and analyzed using the Statistical Package for Social Sciences (SPSS, version 17.0). The associations were assessed using the χ2 test or Fisher’s exact test with Freeman-Halton extension, where appropriate, adopting a significance level α<5%. Results: A total of 93 elderly victims of falls. The most prevalent group was of age equal to or greater than 80 years (47.3%), female (62.4%) ,with incomplete primary education or above (51.6%), no income or income below the poverty level (66.7%), living without a partner (65.6%). The occurrence of falls in the elderly showed an association between age group and sex (p=0.004), marital status (p=0.002), hospitalization (p=0.047) and place of fall (p=0.006). Conclusion: Elderly patients 70 years or older were those who presented in greater proportion to length of stay and, in relation to the place of occurrence of the fall, it was observed that, among the oldest old, stood out a higher percentage falls at home, especially when compared to younger participants.